The Effectiveness of Facilities and Infrastructure Management in Improving Employee Performance at the Human Resources Development Agency of Southeast Sulawesi Province - Muhamad Syarifin Arif; Abd. Azis Muthalib; Nofal Supriaddin (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze (1) The performance of employees of the Human Resources Development Agency of Prov. Southeast Sulawesi; (2) The effectiveness of the management of facilities and infrastructure in improving the performance of employees of the Provincial Human Resources Development Agency. Southeast Sulawesi; (3) Supporting and inhibiting factors in the management of facilities and infrastructure in improving the performance of employees of the Provincial Human Resources Development Agency. Southeast Sulawesi. The analysis tool used is the Analysis Interactive Model by dividing the steps in data analysis activities with several parts, namely data collection, data reduction, data display, and conclusion or verification. This study shows that (1) The performance of employees of the Provincial Human Resources Development Agency. Southeast Sulawesi, which is judged from quality, quantity, timeliness, effectiveness and presence, is good; (2) The effectiveness of the management of facilities and infrastructure in improving the performance of employees of the Provincial Human Resources Development Agency. Southeast Sulawesi, both in terms of completeness, condition, and use, plays an important role in supporting optimal employee performance, including aspects of quality, quantity, punctuality, effectiveness, and attendance; (3) Supporting factors for the management of facilities and infrastructure in improving the performance of employees of the Provincial Human Resources Development Agency. Southeast Sulawesi is a personal or individual factor, a leadership factor and a system factor. While the most important inhibiting factor is human resources.